Metabolic Engineering of Microorganisms for the Production of Flavonoids - Sheng, Huakang; Sun, Xinxiao; Yan, Yajun; Yuan, Qipeng; Wang, Jia; Shen, Xiaolin (Frontiers in Bioengineering and Biotechnology, 2020)
Flavonoids are a class of secondary metabolites found in plant and fungus. They have been widely used in food, pharmaceutical and nutraceutical industries owing to their significant biological activities, such as anti-aging, antioxidant, anti-inflammatory and anti-cancer. According to the report, the global market of flavonoids is growing rapidly and is expected reach to 1.05 billion US dollars in 2021. However, the traditional approaches for the production of flavonoids including plant extraction and chemical synthesis are not economically competitive due to the complicated processes and low products titer and yield. Microbial synthesis of flavonoids from renewable biomass has been considered as a sustainable and environmentally friendly method for large-scale production of flavonoids. Recently, construction of microbial cell factories for efficient biosynthesis of flavonoids has gain much attention. Many novel enzymes, products and pathway optimization strategies have been reported but have yet been informative reviewed so far. In this article, we summarize the recent advances in microbial synthesis of flavonoids including flavanones, flavones, isoflavones, flavonols, flavanols and anthocyanins. We put emphasis on developing pathway construction and optimization strategies to biosynthesize flavonoids and to improve their titer and yield. Then, we discuss the current challenges and future perspectives on successful strain development for large-scale production of flavonoids in an industrial level.